The Advantages of Free Trade Over Tariffs - Asprodites, Emmanuel M.; Block, Walter E. (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
The term paper examines the historic conflict between protectionism and free trade, arguing that unilateral free trade is the superior economic policy. While tariffs are traditionally justified as tools to guard home industries and protect jobs, economic theory and existing evidence confirm that such protectionist behavior ultimately reduces economic efficiency, raises consumer prices, and hurts long-run growth. Drawing from the initial theories of David Ricardo and Adam Smith and Austrian economists today, the paper describes how open markets, specialization, and comparative advantage provide a win-win scenario for trading nations. Historical evidence from case studies like Britain's post-Corn Laws period and the East Asian export-led growth is testimony that countries thrive if free trade is permitted. Lastly, the evidence is in favor of the argument that free trade is not just economically optimal but also ethical, and should be embraced as a means to greater prosperity and global development.